THERMOBAROMETRIC METHOD FOR DETERMINING THE PREMETAMORPHIC NATURE OF QUARTZITE - Kulish Ye.A.; Zakrutkin V.V.; Skripka G.I. (My University, 1989)
We studied quartzite in order to find new ways of reconstructing its primary nature. For this purpose, we chose the quartzites that are widespread in the central part of the Mongolia-Okhotsk mobile belt in virtually all formations from Upper Proterozoic to Permian. The quartzite samples were studied in pressure chambers heated to 950° C. The volumes of evolved gas were recorded in terms of vacuum change. Analysis of the resulting decrepitation diagrams reveals their essential differences. Our method makes it possible to reconstruct the premetamorphic nature of quartzite in considerable detail and thereby avoid the alternative method of solving this problem by reconstructing the conditions under which old sequences were deposited.
Keywords: Proterozoic; Permian; Докембрий::Протерозой; Paleozoic::Permian; Precambrian::Proterozoic; Палеозой::Пермская